Analysis of Brazilian public policies which aim to support participatory construction of the National Plan for Soil and Water Sustainable Management. (5th January 2021) - Stuchi, Julia F.; Hernández, David G.; de Andrade, Aluísio G.; Monteiro, Joyce M. G.; Hissa, Helga R.
Abstract: This study analyzes relevant federal public policies for soil and water conservation in Brazil. The Federal Court of Auditors reported that the lack of a national policy for soil and water conservation in the Country poses a considerable risk of degradation of soil and water resources, despite the existence of legal instruments. This study aims to outline and build upon previous experiences related to the participatory formulation of the new Brazilian National Plan for Soil and Water Sustainable Management (NP). We selected seven current public policies at the federal level involving conservation of soil and water resources in rural areas. We carried out content analysis for each of the selected policies using a qualitative‐interpretive treatment, starting from six analytical axes proposed for the NP. The six axes are Legislation, Prevention, Conservation, Recovery, Monitoring, and Integration. Five keywords were identified for each axis. The analysis produced a score to measure the adherence of keywords in the public policies. This manuscript shows: (a) the importance of all the policies analyzed as significant contributions for the construction of the new NP; (b) the gaps of these policies regarding the six strategic axes provided by the NP; (c) how to turn strengths and gaps of the policies into recommendations and opportunities for a more robust NP. There is need for greater commitment of relevant stakeholders in the construction of the policy and in the decision‐making process to improve the sustainable management of soil and water resources in Brazil.